In Vitro Bacterial Contamination of Amniotic Fluid: Effects on Fluorescence Polarization Lung Maturity Testing. Issue 3 (1995) - Heine, R. Phillip; Harding, Susan; Emmett, Pegi; Ashwood, Edward; Lenke, Roger R.
Abstract : Objective: We sought to determine the effect of bacteria on fluorescence polarization (FPOL) testing of amniotic fluid. Methods: Fusobacterium necrophorum and Escherichia coli were inoculated at concentrations of10 3 and10 6 /ml in amniotic-fluid specimens from 4 patients with no clinical or laboratory evidence of infection. The FPOL results were obtained at inoculation and again at 24 h of incubation. The results were compared using analysis of variance (ANOVA). Results: The FPOL results from inoculated specimens were all within 2% of the uninoculated controls. The specimens incubated with bacteria showed a < 1–19% variation when compared with the time-zero uninoculated controls. However, uninoculated controls incubated for 24 h exhibited a 2–12% variation when compared with the time-zero controls, suggesting that the variation present was not secondary to the bacterial co-incubation. Conclusions: In vitro, neither bacterial inoculation nor prolonged co-incubation influences FPOL results beyond the effect of incubation alone. FPOL appears to be an appropriate test to assess fetal lung maturity in patients in whom intraamniotic infection is a concern.